Preparation, Characterization And Performance Of Polyaniline-Titanium Oxide Composite Pellet For Detection Of Acetone Vapor - Bahru, Raihana (2013)
The present work focuses on the detection of the VOCs with particular emphasis on acetone which is harmful to the environment and human health. The semiconductor based sensor is one of the best VOC sensors which currently available. However, the main drawback of this type of gas sensor is the utilization of high optimum operating temperature (greater than 200oC). An interesting approach for lowering the operating temperature is by incorporating an organic material as the additional sensing material. A conducting polymer known as polyaniline (PANI) was added to titanium oxide (TiO2) by in-situ chemical polymerization method to form PANI-TiO2 composite pellet to be used for detection of acetone vapor. The composite sensor was characterized using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) Spectroscopy, Transmission Electron Microscopy (TEM), Fourier Transformation Infrared Spectroscopy (FTIR), and Surface Analysis (N2 adsorption-desorption). The performances of composite pellets were tested using sensing measurement unit at temperature 27oC - 65oC by releasing the acetone vapor at various concentrations in the range of 100 – 500 ppm. Response Surface Methodology (RSM) was used to optimize the experimental data. A correlation of 3 parameters which are additive loadings, operating temperature and acetone vapor concentration has been considered. It was found that 30wt.% PANI-TiO2 was the best composite pellet which gave the maximum sensitivity. The optimum performance was at 45oC with sensitivity approximately at ~16.19% towards 300 ppm acetone vapor concentration.